E-Service Quality, E-Trust, E-Satisfaction And E-Loyalty In Online Shopping - Pratama, Rekha Agustiyanto; Prasetyo, Wishnu Budi; Ramli, Abdul Haeba (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Research on e-loyalty refers to the level of loyalty or e-loyalty at the level of customer loyalty or loyalty to service platforms, or company digital products because internet and technological developments have changed the way businesses interact with customers. the purpose of this research is to know the direct effect of e-service quality and e-trust on e-loyalty, then to know the direct effect, e-trust and e-satisfaction, then to find out how e-service quality, e-trust, e-satisfaction affect e-loyalty to online shopping. Data was collected through a questionnaire, the questionnaire was distributed via social media using the Google form, the population of this study was an online shopping application user. questionnaire collected 110 respondents, the sampling is non-probability with a purposive sampling procedure. In this study using a quantitative approach. The results of the study are E-service Quality with e-Satisfaction has no positive effect, e-Trust with e-Satisfaction has a positive effect on e-loyalty, e-service Quality has no positive effect on e-loyalty, e- trust has no positive effect on e-loyalty, E-Satisfaction with E-Loyalty has no positive effect, E-Trust on E-Loyalty mediated by E-Satisfaction has no positive effect, E-Service Quality on E-Loyalty mediated by E -Satisfaction has no positive effect. This research is expected to be a reference for online shop companies in providing electronic services to their customers. Keywords: e-service quality, e-trust, e-Satisfaction; e-loyalty